Pengembangan Ensiklopedia Digital Hewan Vertebrata Berbasis Android Studio 2.2 untuk Kelas X SMA: Development of Digital Encyclopedia Vertebrate Animals-Based Android Studio 2.2 for Class X of Senior High School - Sumadi Sumadi; Evita Anggereini; Upik Yelianti (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2017)
The proper media will easy students to understand subject matter in class. This study aims to develop digital media in the form of encyclopedia for vertebrate as a source of student learning. The This research and development produce digital encyclopedias of vertebrate that is used as media in learning biology. The model used in this study is the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation). Products that have been developed are then validated by material experts and media experts. The validation process by the two experts was carried out three times before finally the prouduct was declared feasible to be tested both for teachers and students. The response showed that biology teacher in the SMA 4 Muaro Jambi assesed the product as "very good". The results of the small group trials obtained a percentage value of 96.3% (very good category), while the large group trials obtained a percentage value of 84.6% (very good category). Based on the results of these trials, overall the digital encyclopedia of vertebrate animals based on Android Studio is categorized very good to be used as one of the learning resources in learning biology in high school.